Anthropometric Parameters of Newborn Infants - Das, Jagadish C (Journal of Chittagong Medical College Teachers’ Association, 2013)
Bangladesh is a densely populated developing country. Majority of the population live here in the rural community. Illiteracy, poverty and malnutrition are widely prevalent here. Health service facilities even for the neonate are not satisfactory. Anthropometric parameters at birth are considered to be of great value. Incidence of low birth weight is high in our area. Though study on anthropometric parameters on neonate in our country had been undertaken in the past, attempt on various anthropometric parameters at a time are not much. Here, an attempt has been taken to study maximum anthropometric parameters on neonates at a time so that an idea can get on these parameters. It was a descriptive cross-sectional study on 560 newborn infants over a period of one year six months. In this work, mean gestational age of neonate was 37.9±10 week. Mean birth weight was 2507 580 gm but mean birth weight of term neonates were 2770 gm. Approximately 47% babies were low-birth weight. Though observed mean birth length was 48.1 = 3.1cm, the average length for term babies was 49.4±1.8 cm. Values of observed mean mid-arm circumference, head circumference, chest circumference, abdominal girth and calf circumference were 9±1.3 cm, 32.8±2.0 cm, 30.2±2.9 cm, 27.7±2.6 cm and 10.11.2 cm respectively. All anthropometric parameters were marginally more in male than in female babies. JCMCTA 2012 ; 23 (2): 38-41